Analysis Of Calcium Levels in Wet and Dried Anchovies at Traditional Markets in Bekasi City - Safitri, Fadliyah Rani; Sari, Elfira Maya; Nurfajriah, Siti (Chempublish Journal, 2023)
Anchovy is a food that is widely consumed by the people of Indonesia because it has high quality and affordable prices for the middle and lower economic class. Anchovy as a source of calcium is very good for preventing osteoporosis, the formation and maintenance of bones and teeth, smooth muscle function, and the nervous system. The purpose of this study was to determine the calcium levels of wet anchovies and dried anchovies sold in traditional markets in the city of Bekasi. Determination of calcium content of wet anchovies and dried anchovies can be determined using atomic absorption spectrophotometry (AAS). Data were analyzed using descriptive analysis. The results of the analysis of the highest calcium levels in wet anchovies were 653.05 mg/100g and the lowest was 517.56 mg/100g. The highest calcium level in dried anchovies is 611.02 mg/100g and the lowest is 148.33 mg/100g. These results indicate that there are differences in calcium levels in wet anchovies and dried anchovies. This occurs due to the presence of water content and salt content in anchovy which affects the high and low calcium Â results in the analysis.